2013
DOI: 10.2965/jwet.2013.497
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection Using Pressurized Carbon Dioxide Microbubbles to Inactivate Escherichia coli, Bacteriophage MS2 and T4

Abstract: This study investigated the potential application of pressurized CO 2 for water disinfection. Under supporting high pressure, a high volume of CO 2 microbubbles were produced in a liquid environment. Specifically, the inactivation effects of CO 2 against Escherichia coli, bacteriophage MS2 and T4 were examined at equal pressures (0.3 -0.9 MPa) and temperatures. The optimum conditions were found to be 0.7 MPa and an exposure time of 25 min. Under identical treatment conditions, a greater than 5.0 log reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Moreover, at high temperature, proteins more easily denatured and the components of external membranes are disintegrated and broken down, so that CO 2 molecules more easily penetrate into the lipid phase and cytoplasm. Most of the recent studies found that increasing temperature led to more effective microorganism inactivation (Kamihira et al, 1987;Dillow et al, 1999;Zhang et al, 2006;Wu et al, 2007;Kobayashi et al, 2009b;Garcia-Gonzalez et al, 2010;Ferrentino et al, 2010;Vo et al, 2013bVo et al, , 2014. However, because rising temperature also decreases the CO 2 solubility in water, a temperature may be reached where no further improvement is gained.…”
Section: Saccharomyces Cerevisiae Inactivationmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, at high temperature, proteins more easily denatured and the components of external membranes are disintegrated and broken down, so that CO 2 molecules more easily penetrate into the lipid phase and cytoplasm. Most of the recent studies found that increasing temperature led to more effective microorganism inactivation (Kamihira et al, 1987;Dillow et al, 1999;Zhang et al, 2006;Wu et al, 2007;Kobayashi et al, 2009b;Garcia-Gonzalez et al, 2010;Ferrentino et al, 2010;Vo et al, 2013bVo et al, , 2014. However, because rising temperature also decreases the CO 2 solubility in water, a temperature may be reached where no further improvement is gained.…”
Section: Saccharomyces Cerevisiae Inactivationmentioning
confidence: 93%
“…Increasing pressure accelerates the CO 2 diffusivity into cell membranes and its solubility in cell cytoplasm. For the same reduction ratio of microorganisms, increasing the working pressure enables a shorter exposure time to treatment process (Kumugai et al, 1997;Erkmen, 2000a,b,c;Garcia-Gonzalez et al, 2010;Vo et al, 2013bVo et al, , 2014. However, excessive pressure does not strongly increase bacterial deaths due to saturation limitations of CO 2 in the suspension phase (Spilimbergo and Bertucco, 2003).…”
Section: Saccharomyces Cerevisiae Inactivationmentioning
confidence: 97%
“…In recent years, pressurized CO 2 has shown great potential as a sustainable disinfection technology in water and wastewater treatment applications [16][17][18][19][20][21][22] largely because this method does not generate DBPs [9,22]. Kobayashi et al [16,17] employed CO 2 microbubbles in the treatment of drinking water and succeeded in inhibiting Escherichia coli within 13.3 min.…”
Section: Introductionmentioning
confidence: 99%
“…However, the pressure (10 MPa) and temperature (35-55°C) requirements for effective inactivation [16,17] are still high from a practical standpoint. Our research group has developed a novel method that uses low-pressure CO 2 treatments (0.2-1.0 MPa) based on technology that produces high amounts of dissolved gas in water to inactive bacteria and bacteriophages in freshwater [19][20][21] and seawater [23,24]. Cheng et al [19] suggested that the sudden discharge and resulting reduction of pressure could cause cells to rupture via a mechanical mechanism, and further, that this would be lethal to cells at high levels of dissolved CO 2 at 0.3-0.6 MPa and room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation